2022
DOI: 10.1111/anae.15847
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pre‐operative anaemia in surgical patients: a retrospective, observational, multicentre study in Germany

Abstract: Anaemia is a risk factor for several adverse postoperative outcomes. Detailed data about the prevalence of anaemia are not available over a long time-period in Germany. In this retrospective, observational, multicentre study, patients undergoing surgery in March in 2007March in , 2012March in , 2015March in , 2017March in and 2019 were studied. The primary objective was the prevalence of anaemia at hospital admission. The secondary objectives were the association between anaemia and the number of units of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…[48] However, other studies have not found a signi cant association between blood transfusions and survival outcomes in patients with gastric cancer or hospital LOS. [49,50] Given these risks, it is recommended that blood transfusions are to be used judiciously and alternative strategies such as erythropoietin-stimulating agents and iron supplementation, should be considered to reduce the need for blood transfusions in the perioperative period. [51][52][53][54] Prolonged LOS is associated with preoperative, intraoperative and post-operative factors.…”
Section: Discussionmentioning
confidence: 99%
“…[48] However, other studies have not found a signi cant association between blood transfusions and survival outcomes in patients with gastric cancer or hospital LOS. [49,50] Given these risks, it is recommended that blood transfusions are to be used judiciously and alternative strategies such as erythropoietin-stimulating agents and iron supplementation, should be considered to reduce the need for blood transfusions in the perioperative period. [51][52][53][54] Prolonged LOS is associated with preoperative, intraoperative and post-operative factors.…”
Section: Discussionmentioning
confidence: 99%
“…32 However, studies have shown that transfusion did not reverse the harms of perioperative anemia in elderly hip fracture patients, and it is associated with poor outcomes such as subsequent infection, fluid overload, prolonged hospital stays, and increased mortality. [33][34][35] Given the shortage of blood supply, restrictive transfusion (70-90 g/L) may be a viable alternative that can reduce transfusion rates by 39-43% compared to unrestricted transfusion (90-110 g/L) and does not increase risk of complications such as myocardial infarction or mortality. 35,36 Therefore, the American Academy of Orthopaedic Surgeons (AAOS) clinical practice guidelines recommend a transfusion threshold of no higher than 80 g/L in patients with hip fractures.…”
Section: Clinical Implicationmentioning
confidence: 99%
“…Iron deficiency (ID) is still the top-ranking cause of anemia in the general population worldwide [ 2 ]. In preoperative patients, the prevalence of ID ranges from 23 to 33% [ 3 , 4 ], with a wide variation between surgical fields (e.g., gynecology (59%), plastic surgery (11%)) [ 4 ]. Preoperative anemia is associated with an increased risk of allogeneic blood transfusions, length of hospital stay, morbidity, and mortality [ 4 , 5 ] making ID an important target to diagnose and treat before elective surgery [ 6 ].…”
Section: Introductionmentioning
confidence: 99%